Salmonella spp. and total bacteria count contamination in traditional markets in Vietnam: a baseline assessment from a food safety randomized controlled trial study - Trang Le-Thi-Huyen (International Livestock Research Institute, 2024)
The objectives of the study were to assess the levels of microbiological contamination (Salmonella and total bacteria count) in fresh pork sold at traditional markets in Vietnam, and assess the association between contamination of pork and vendors’ food safety hygiene practices.